Ideology, Ceremony and Calendar in Pre-Contact Hawaiâ€˜i: Astronomical Alignment of a Stone Enclosure on Oâ€˜ahu Suggests Ceremonial Use during the Makahiki Season - Gill, Timothy M.; Kirch, Patrick V.; Ruggles, Clive; Baer, Alexander (Waka Kuaka, 2015)
The Hawaiian people before Western contact gathered at special places during the Makahiki period, a time that was sacred to the god Lono, and during which sports, games and other ceremonies took place. Archaeological excavation and archaeoastronomical investigation together suggest that an approximately 40 m2 rock enclosure in the uplands of Honouliuli on the island of Oâ€˜ahu was such a special gathering place. Radiocarbon dating indicates that the enclosure was most likely constructed between the late AD 1500s and early AD 1600s, with a notable period of use during the mid-AD 1600s. The archaeoastronomical evidence supports this conclusion, in that the enclosure is precisely aligned upon the horizon rising point in AD 1600 of the Pleiades star cluster (Makaliâ€˜i in Hawaiian), whose first appearance each November marked the beginning of the four-month Makahiki â€œannnual harvestâ€ period dedicated to the god Lono. That time period saw the peaking and stabilisation of population on Oâ€˜ahu, and the expansion of settlements into marginal environmental zones such as Honouliuli. A significant number of temples built around the same time on the island of Maui are oriented in a similar manner.